Predictors of Vaginal Delivery Following Stimulation of Uterine Contractions for Term Premature Rupture of Membranes - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Premature rupture of membranes (PROM) is a significant event as it may lead to maternal complications, increased operative procedure, neonatal morbidity, and mortality.Aim:To determine the predictors of successful vaginal delivery in pregnant women undergoing stimulation of uterine contractions following premature rupture of membranes (PROM).Settings and Design:This prospective cohort study was conducted at the University of Benin Teaching Hospital, Benin City, Nigeria.Materials and Methods:Seventy-four pregnant women between the gestational ages of 37 weeks and 41 weeks with a live singleton fetus in cephalic presentation and no contraindication to vaginal delivery who had stimulation of uterine contractions following term PROM were included in this study. The main outcome measure was the route of delivery.Statistical Analysis:The analysis was done with IBM statistical package for social science (SPSS) Statistics v21, and aPvalue ≤0.05 was considered statistically significant.Results:Sixty-two (83.8%) women had a vaginal delivery. The mean age and gestational age were 29.76 ± 3.69 years and 39.04 ± 1.15 weeks, respectively. The chance of vaginal delivery was increased with BMI